Reliability of Different Bending Test Methods for Dental Press Ceramics - Miura D; Ishida Y; Miyasaka T; Aoki H; Shinya A (MDPI, 2025)
Objective: This study investigates the reliability of different flexural tests such as three-point-bending, four-point bending, and biaxial tests, in strengthening the dental pressed ceramics (DPCs) frequently used in clinical applications. Methods: The correlations between the three types of bending tests for DPCs were investigated. Plate-shaped specimens for the three-point and four-point bending tests and a disc-shaped specimen for the biaxial bending test were prepared. Each bending test was conducted using a universal testing machine. Results: The results for six DPCs showed that the flexural strength in descending order were the three-point flexural strength, biaxial flexural strength, and four-point flexural strength, respectively. Then, a regression analysis showed a strong correlation between each of the three test methods, with the combination of four-point and biaxial flexural strength showing the highest values. The biaxial flexural strength was not significantly different in the Weibull coefficient (m) compared to the other tests, with the narrowest range considering the 95% interval. The biaxial bending test was found to be suitable for materials with small plastic deformation from the yield point to the breaking point, such as DPCs.